Developing Discipline among Students through Social-Emotional Learning: A New Model to Prevent and Reduce Behavior Problems - Ching, Lee Moi; ., Hadijah Jaffri (Journal of Education and Vocational Research, 2015)
The disciplinary problem in schools is a major concern for government, educators, parents and society in Malaysia. Knowing that discipline problems will be dealt with fairly and consistently has been shown to have a dramatic impact on student well-being and achievement. This study discussed the discipline issues in Malaysia; the affects of reactive and punitive approach; root cause attributing to the students discipline problems; how to cope with the disciplinary problems; and using social-emotional learning (SEL) to develop discipline among students. SEL is a promising approach that is able to reduce risky behaviours, increase desirable behaviours and promoting positive development.